Assessment of Cognitive Scales to Examine Memory, Executive Function and Language in Individuals with Down Syndrome: Implications of a 6-month Observational Study - Liogier d'Ardhuy, Xavier; Edgin, Jamie O.; Bouis, Charles; de Sola, Susana; Goeldner, Celia; Kishnani, Priya; Nöldeke, Jana; Rice, Sydney; Sacco, Silvia; Squassante, Lisa; Spiridigliozzi, Gail; Visootsak, Jeannie; et al. (Frontiers in Behavioral Neuroscience, 2015)
Down syndrome (DS) is the most commonly identifiable genetic form of intellectual disability. Individuals with DS have considerable deficits in intellectual functioning (i.e., low intellectual quotient, delayed learning and/or impaired language development) and adaptive behavior. Previous pharmacological studies in this population have been limited by a lack of appropriate endpoints that accurately measured change in cognitive and functional abilities. Therefore, the current longitudinal observational study assessed the suitability and reliability of existing cognitive scales to determine which tools would be the most effective in future interventional clinical studies. Subtests of the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS), Cambridge Neuropsychological Test Automated Battery (CANTAB), and Clinical Evaluation of Language Fundamentals-Preschool-2 (CELF-P-2), and the Observer Memory Questionnaire-Parent Form (OMQ-PF), Behavior Rating Inventory of Executive Function®–Preschool Version (BRIEF-P) and Leiter International Performance Scale-Revised were assessed. The results reported here have contributed to the optimization of trial design and endpoint selection for the Phase 2 study of a new selective negative allosteric modulator of the GABAA receptor α5-subtype (Basmisanil), and can be applied to other studies in the DS population.